2013
DOI: 10.1038/nm.3353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and acute CPEB1 depletion ameliorate fragile X pathophysiology

Abstract: Fragile X Syndrome (FXS), the most common cause of inherited mental retardation and autism, is caused by transcriptional silencing of Fmr1, which encodes the translational repressor protein FMRP. FMRP and CPEB, an activator of translation, are present in neuronal dendrites, are predicted to bind many of the same mRNAs, and may mediate a translational homeostasis that, when imbalanced, results in FXS. Consistent with this possibility, Fmr1-/y Cpeb−/− double knockout mice displayed significant amelioration of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(122 citation statements)
references
References 41 publications
9
108
0
Order By: Relevance
“…In line with this observation, genetic or pharmacological reduction of central molecules involved in the regulation of general mRNA translation (mTOR [121], S6K1 [111], tuberous sclerosis 2 [160]) and molecules involved in the mRNA translation of select targets (cytoplasmic Poly(A)-binding protein [161]) have been used successfully in the mouse model to rescue many phenotypes. Future studies will have to show if general reduction of mRNA translation is a safe therapeutic strategy in humans.…”
Section: Neurotransmitter Receptors Versus Intracellular Signaling Anmentioning
confidence: 86%
See 1 more Smart Citation
“…In line with this observation, genetic or pharmacological reduction of central molecules involved in the regulation of general mRNA translation (mTOR [121], S6K1 [111], tuberous sclerosis 2 [160]) and molecules involved in the mRNA translation of select targets (cytoplasmic Poly(A)-binding protein [161]) have been used successfully in the mouse model to rescue many phenotypes. Future studies will have to show if general reduction of mRNA translation is a safe therapeutic strategy in humans.…”
Section: Neurotransmitter Receptors Versus Intracellular Signaling Anmentioning
confidence: 86%
“…Moreover, it will be important to identify more robust and reliable behavioral defects. Here, recent advances in analyzing social behavior and social interactions in FXS mice may hold some promise [119,161,212].…”
Section: Behavioral and Cognitive Phenotypes In The Fxs Mouse Modelmentioning
confidence: 99%
“…While control mice take more time or even refuse to enter the dark compartment, because they associate it with the shock of their paws, the Fmr1 KO mice show a range of behavioral responses. It has been reported that the Fmr1 KO mice showed a deficit in associative learning Michalon et al 2012), but also normal performance (Bakker 1994;Dolen et al 2007;Veeraragavan et al 2012;Udagawa et al 2013). However, memory extinction was exaggerated in the Fmr1 KO mice (Dolen et al 2007;Michalon et al 2012), as observed by shorter latencies to enter the dark compartment.…”
Section: Associative Learningmentioning
confidence: 99%
“…Initially identified as maternal mRNA regulators during early embryonic development (Richter and Lasko 2011;Weill et al 2012), it is now clear that CPEBs are key mediators of cellular homeostasis in somatic tissues, regulating important biological processes such as cell proliferation, senescence, cell polarity, and synaptic plasticity. Consequently, when misregulated, they contribute to the development of a variety of pathological manifestations, such as tumor development, memory defects, and insulin resistance (Berger-Sweeney et al 2006;Alexandrov et al 2012;Ortiz-Zapater et al 2012;Weill et al 2012;Udagawa et al 2013).…”
mentioning
confidence: 99%